Who was Eleanor Roosevelt? - Thompson, Gare.; Wolf, Elizabeth, 1954- (New York : Grosset & Dunlap, 2004)
A biography of the woman who served as First Lady for the longest time, and who was the first President's wife to speak out about important issues of the day, by writing newspapers articles and books, giving radio interviews and speeches, and teaching classes.
Angela Misa
Keywords: Roosevelt, Eleanor, -- Juvenile literature; Roosevelt, Eleanor; Presidents' spouses -- United States -- Biography -- Juvenile literature; First ladies; Women -- Biography